The effect of body composition on cycling power during an incremental test in young athletes - Schomöller, A.; Schugardt, M.; Kotsch, P.; Mayer, F. (The Journal of Strength and Conditioning Research, 2021)
As body composition (BC) is a modifiable factor influencing sports performance, it is of interest for athletes and coaches to optimize BC to fulfill the specific physical demands of one sport discipline. The purpose of this study is to test the impact of body fat (BF) and fat-free mass (FFM) on aerobic performance in young athletes. Body composition parameters were evaluated among gender and age groups of young athletes undergoing their mandatory health examination. The maximal power (in Watts per kilogram body mass) of a stepwise incremental ergometer test was compared between 6 BC types: high BF, high FFM, high BF and high FFM, normal BC values, low BF, and low FFM. With increasing age (11-13 vs. 14-16 years) BF decreased and FFM increased in both genders. Both BC parameters, as well as body mass, correlated moderately with performance output (r = 0.36-0.6). Subjects with high BF or high FFM or both had significantly lower ergometer test results compared with those with low BF and FFM in all age and gender groups (p < 0.05). The finding that high levels of BF and FFM are detrimental for cycle power output is important to consider in disciplines that demand high levels of aerobic and anaerobic performance.